The Influence of Customer Knowledge Management on Sustainable Promotion - sadkan Abd-Alhasan, Ruaa; Abdullah Mohammed , Atheer (Journal of Economics and Administrative Sciences, 2023)
This research has investigated the effect of the customer knowledge management CKM in sustainable promotion SP. The research conducted a quantitative method on a sample of employees in the Al-Furat State Company for Chemical Industries affiliated / the Ministry of Industry and Minerals in Iraq. The research’s problem presented a set of questions, one of the most important was (is there a relation and impact between the dimensions of customer knowledge management and sustainable promotion). The aim of the research is to identify the extent to which customer knowledge management activities are applied in understudy organization. This research adopted the questionnaire as a main instrument to collect information from (140) participants in various administrative levels (top management, middle, and executive). One of the most important results of the research was the existence of a relation and effect between the dimensions of customer knowledge management and sustainable promotion.  Also, the findings of the current research revealed a great interest in customer knowledge management and its dimensions (knowledge from the customer, about the customer, of the customer, and joint construction) with sustainable promotion. According to these findings, the research recommended supporting CKM in the researched company through promoting activities related to understanding the needs and desires of customers and providing them with sustainable products.